2020
DOI: 10.1088/1742-6596/1480/1/012071
|View full text |Cite
|
Sign up to set email alerts
|

Development of HOTS (higher order thinking skills) test instruments for the concept of fluid and harmonic vibrations for high schools

Abstract: The thinking ability of Indonesian students is still relatively low, this can be seen from the ranking of Indonesia based on the results of TIMSS in 2015. To improve students ‘thinking abilities and provide reinforcement to students’ abilities, one of the efforts is to equip students with higher-order thinking skills by using questions HOTS is based on the Borg and Gall development model. A Higher Order Thinking Skill (HOTS) instrument has been developed that is subject to a valid and reliable fluid subject in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 4 publications
1
4
0
1
Order By: Relevance
“…So that in this question it was found that students who experienced misconceptions were 74.45%. This is in line with the previous research conducted by Wiyono [26] and Akhsan, et al [27] which amounted to 54.8%.…”
Section: Discussionsupporting
confidence: 93%
“…So that in this question it was found that students who experienced misconceptions were 74.45%. This is in line with the previous research conducted by Wiyono [26] and Akhsan, et al [27] which amounted to 54.8%.…”
Section: Discussionsupporting
confidence: 93%
“…The E-module which will be developed also contains HOTS questions related to the concept of static fluids in everyday life. This has a goal that is in line with Thomas and Thorne ( 2012) in (H. Akhsan et al, 2020) which states that HOTS can be learned and can improve students' skills and character.…”
Section: Introductionmentioning
confidence: 63%
“…Feature On the value of the character of responsibility and discipline, this emodule has a "Come on Do it" feature. Various HOTS questions are presented regarding the concept of static fluids in everyday life so that we can find out the ability and students' insights about the concept of static fluids which states that HOTS can be learned and can improve students' skills and character (H. Akhsan et al, 2020). It is hoped that this feature can instill the character values of responsibility and discipline in students.…”
Section: Figure 8 Features Did You Knowmentioning
confidence: 99%
“…di sini terjadi integrasi konsep sains dengan proses sains mahasiswa berperan aktif mendiskusikan prosedur, persiapan materi, menentukan variable control dan pengukuran, pada kegiatan ini dosen memantau ketepatan aktivitas mahasiswa; ketiga proses investigasi, pada proses ini melalui koleksi dan mempresentasikan data mahasiswa dapat membaca data secara akurat, mengorganisasi data dalam cara yang logis dan bermakna, dan memperjelas hasil penyelidikan dan keempat proses membangun pengetahuan, dalam proses ini, melalui refleksi-konstruksi prediksi, yang dilakukan dengan eksperimen dapat meningkatkan keterampilan berpikir [11], [12]. Untuk itu mahasiswa harus menghubungkan antara interpretasi data dengan interpretasi ilmiah yang diterima mahasiswa dapat mengaplikasikan pemahamannya pada situasi baru yang mengembangkan inferens, generalisasi dan prediksi, dosen bertukar pendapat (sharing) terhadap pemahaman mahasiswa [13].…”
Section: Pendahuluanunclassified